2020
DOI: 10.21203/rs.3.rs-90827/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A U.S. Isolate of Theileria Orientalis, Ikeda Genotype, is Transmitted to Cattle by the Invasive Asian Longhorned Tick, Haemaphysalis Longicornis

Abstract: BACKGROUNDTheileria orientalis is a tick-borne hemoparasite that causes anemia, ill thrift, and death in cattle globally. The Ikeda strain of T. orientalis is more virulent than other strains, leading to severe clinical signs and death in less than 5% of affected animals. Within the Asia-Pacific region, where it affects 25% of Australian cattle, T. orientalis Ikeda has a significant economic impact on the cattle industry. In 2017, T. orientalis Ikeda was detected in a cattle herd in Albermarle County, Virginia… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…However, we continued to detect the pathogen in host-seeking H. longicornis during the 2020 sampling period, further supporting our previous results from 2019 (Thompson et al, 2020b). In addition, recent experimental work has shown that H. longicornis is a competent vector for this pathogen in the United States, warranting continued molecular surveillance for T. orientalis in H. longicornis in other states, especially in regions near cattle operations (Dinkel et al, n.d.). The other apicomplexan detected in H. longicornis was a Hepatozoon sp.…”
Section: Discussionmentioning
confidence: 99%
“…However, we continued to detect the pathogen in host-seeking H. longicornis during the 2020 sampling period, further supporting our previous results from 2019 (Thompson et al, 2020b). In addition, recent experimental work has shown that H. longicornis is a competent vector for this pathogen in the United States, warranting continued molecular surveillance for T. orientalis in H. longicornis in other states, especially in regions near cattle operations (Dinkel et al, n.d.). The other apicomplexan detected in H. longicornis was a Hepatozoon sp.…”
Section: Discussionmentioning
confidence: 99%
“…13 T. orientalis ikeda has recently been identified in cattle in Virginia, affecting animals that were also parasitized with H. longicornis ticks; 10 this tick has been confirmed as a competent vector for the Virginia T. orientalis ikeda . 7 The animals that were clinically affected in this outbreak presented with the typical signs of anemia, icterus, and general malaise. In Virginia, this clinical presentation is identical to the blood infection caused by the bacterium Anaplasma marginale.…”
Section: Introductionmentioning
confidence: 97%